Compound Mask for Divergent Wave Imaging in Medical Ultrasound - Zahraa Alzein; Marco Crocco; Daniele D. Caviglia (IEEE Access)
Divergent wave imaging with coherent compounding allows obtaining broad field-of-view and higher frame rate with respect to line-by-line insonification. However, the spatial and contrast resolution crucially depends on the weights applied in the compound phase, whose optimization is often cumbersome and based on trial and error. This study addresses these limitations by introducing a closed-form approach that maps the transmit apodization weights used in synthetic aperture imaging into the compound mask applied to divergent wave imaging. The approach draws inspiration from a successful technique developed for plane wave imaging, leveraging synthetic aperture imaging as a reference due to its superior image quality. Unlike the previous work on plane waves, the proposed approach is not limited to linear probe geometries but works seamlessly also with convex ones, thus expanding the scope of applicability of divergent wave imaging. Moreover, it handles arbitrary spatial arrangements of virtual sources generating divergent waves. The approach has been validated through simulated data using both linear and convex probes, demonstrating that the Full Width at Half Maximum (FWHM) in Divergent Wave Linear Array (DWLA) increased by 7.5% at 20 mm and 9% at 30 mm compared to Synthetic Aperture Linear Array (SALA). For Divergent Wave Convex Array (DWCA), the increase was 1.64% at 20 mm and 26.56% at 30 mm compared to Synthetic Aperture Convex Array (SACA), witnessing the method’s effectiveness.